2001
DOI: 10.1046/j.1440-1592.2001.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 and interleukin-13 induce fibronectin production by human lung fibroblasts

Abstract: Background: Interleukin (IL)-4 and IL-13, which play a role in the production of allergic inflammation, can activate fibroblasts to elicit a variety of cellular functions. However, the effect of IL-4 and IL-13 on fibronectin production by human lung fibroblasts (HLF) has not been determined. In the present study, we examined the effect of IL-4 and IL-13 on fibronectin production by HLF in order to clarify these issues. Methods: We stimulated HLF with various concentrations of IL-4 and IL-13 for 12, 24, 48 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Therefore, we co-cultured in vitro differentiated Th9 cells with Th0 cells and found that Th9 cells indeed promoted the differentiation of Th0 cells to Th2 cells. In addition, IL-4 can also promote fibroblast proliferation and activation [10,47]. We then examined the effects of Th9 cells on fibroblasts in vitro and found that Th9 cells promoted collagen secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we co-cultured in vitro differentiated Th9 cells with Th0 cells and found that Th9 cells indeed promoted the differentiation of Th0 cells to Th2 cells. In addition, IL-4 can also promote fibroblast proliferation and activation [10,47]. We then examined the effects of Th9 cells on fibroblasts in vitro and found that Th9 cells promoted collagen secretion.…”
Section: Discussionmentioning
confidence: 99%